White Bile Detected During Endoscopic Retrograde Cholangiopancreatography: A Rare Phenomenon and Its Clinical Implications - Kurt, İdris and Taymez, Yalçın and Karadağ, Görkem (Turkish Journal of Gastroenterology, 2025)
Cite this article as: Kurt , Taymez Y, Karada& G. White bile detected during endoscopic retrograde cholangiopancreatography:A rare phenomenon and its clinical implications. Turk J Gastroenterol. 2025;36(6):408-409.